Telomere length in granulosa cells and leukocytes: a potential marker of female fertility? A systematic review of the literature - Anne-Julie Fattet; Simon Toupance; Simon N. Thornton; Nicolas Monnin; Jean-Louis Guéant; Athanase Benetos; Isabelle Koscinski (BMC, 2020)
Abstract In the context of a continuously increased delay of motherhood and of an increase of the incidence of premature ovarian failure, it is of the greatest interest to dispose of a predictive marker of the duration of the fertility window. Unfortunately, current available markers of women's fertility (hormonal rates or echography count of small follicles) have a poor predictive value of premature ovarian failure. In the last ten years, some studies have suggested that telomere length may be correlated with premature ovarian failure, but the results of these studies are contradictory. In accordance with guidelines from Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA), this systematic review of the literature selected studies evaluating telomere length or telomerase activity in granulosa cells and/or in leukocytes as a premature ovarian failure marker. Five publications (252 premature ovarian failure patients) were included in this review of experimental evidence. Two of them studied telomere length and/or telomerase activity in granulosa cells and 4 in leukocytes in women with premature ovarian failure. For each study, authors determined if there was a positive or a negative correlation between telomeric parameters and premature ovarian failure. 3 studies (178 premature ovarian failure patients) found shorter telomere length in granulosa cells and/or leukocytes and/or lower telomerase activity in premature ovarian failure patients. 2 studies (74 premature ovarian failure patients) presented contradictory results about the correlation of leucocyte telomere length with premature ovarian failure. Shorter telomeres and diminished telomerase activity in granulosa cells appear to be associated with ovarian insufficiency. However, the number of studies and of subjects within are low and the methodology questionable. The confirmation of these results is essential with more subjects, better defined populations and more adapted methodology, in order to consider telomere length in granulosa cells and/or in leucocytes as an early and reliable marker for the decline of ovarian function.